Analisis Produk Simpan Pinjam Dan Pembiayaan Syariah Dalam Perspektif Hukum Syariah (Studi Pada Koperasi Swadaya Pribumi Klapanunggal Kabupaten Bogor) - Apipah, Neng Ulpa; Munir, Muhammad Misbakul; Muti, Ahmad (Journal of Computer Science and Information System(JCoInS), 2024)
This thesis is entitled "Analysis of Sharia Savings and Loans and Financing Products In Sharia Law Perspective (Study of Indigenous Self-Help Cooperatives Klapanunggal Bogor Regency)” this is descriptive qualitative research, namely The researcher explains the facts in the field to determine their suitability with sharia standards in the process of implementing the products contained in Klapanunggal Indigenous Self-Help Cooperative, Bogor Regency. This thesis is focused research on the Sharia Savings and Loans and Financing Unit. In the product divided into 2 (two), namely financing products and savings products. Results research shows that the Klapanunggal Indigenous Self-Help Cooperative inits implementation is in accordance with sharia. Rukun, terms and conditions of the contract are created based on the DSN-MUI Fatwa (National Sharia Council - Ulama Council Indonesia) which has been adapted to the Koran, al-Hadith and the consensus of the ulama.